Syarh Al-Isyārī: The Sufi Approach to Interpreting the Prophet’s Hadith - Viki Junianto; Iqbal Nursyahbani; Ahmad Nurhamdani; Achmad Roziqi (UIN Syarif Hidayatullah Jakarta, 2025)
The syarḥ al-ishyārī approach is a method of hadith interpretation developed within the Sufi tradition, emphasizing texts' inner and symbolic meanings. However, this approach is often seen as deviating from the literal intent of the hadith. This study aims to examine the forms of syarḥ al-ishyārī within the Sufi tradition and evaluate its validity using five criteria formulated by al-Zurqānī. A qualitative research method based on library research was used, analyzing works such as Futūḥāt al-Makkiyyah, Iḥyā' 'Ulūm al-Dīn, and Mir’āt al-Ḥaqā’iq. The findings show that syarḥ al-ishyārī is acceptable if it does not contradict the apparent meaning, is free from weak interpretations, and aligns with both transmitted and rational evidence. This study recommends a cautious and methodological approach to Sufi interpretations of hadith. The main conclusion suggests that syarḥ al-ishyārī is a valid derivative interpretation when it adheres to strict scholarly boundaries.